Case report: Novel TBX5-related pathogenic mechanism of Holt–Oram syndrome - Lang, Yuheng; Zheng, Yue; Qi, Bingcai; Zheng, Weifeng; Zhao, Chengxiu; Zhai, Hu; Wang, Gang; Luo, Zhiqiang; Li, Tong (Frontiers in Genetics, 2023)
Introduction: Holt–Oram syndrome (HOS) is a rare genetic disorder characterized by upper limb abnormalities, congenital heart defects, and/or conduction abnormalities. Sequence alteration of T-box transcription factor 5 (TBX5) is correlated with the incidence of HOS. Case description: We present the case of a 24-year-old female with upper limb alterations (congenital dysplasia in the wrist and elbow joints) and an anomalous left main trunk arising from the right coronary sinus. The patient inherited a base T (reference C) at rs883079 from her mother and base C (reference T) at rs10850326 from her father, both of which belong to the 3′-untranslated region (UTR) of the TBX5 gene; no alterations in TBX5 expression or single-nucleotide polymorphisms (SNPs) in other exon areas were found. We explored the effects of TBX5 on cardiomyocytes using the HL-1 cell line and TBX5-knockdown cells. Discussion: Quantitative polymerase chain reaction analysis demonstrated that TEKT2, TEKT4, and SPTB expression decreased after TBX5 knockdown, while chromatin immunoprecipitation analysis further revealed that TBX5 binds to the TEKT2, TEKT4, and SPTB promoter regions to promote gene transcription. Our findings support a novel TBX5-related pathogenic mechanism in HOS.